If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5v + 3)(9 + v) = 0 Reorder the terms: (3 + 5v)(9 + v) = 0 Multiply (3 + 5v) * (9 + v) (3(9 + v) + 5v * (9 + v)) = 0 ((9 * 3 + v * 3) + 5v * (9 + v)) = 0 ((27 + 3v) + 5v * (9 + v)) = 0 (27 + 3v + (9 * 5v + v * 5v)) = 0 (27 + 3v + (45v + 5v2)) = 0 Combine like terms: 3v + 45v = 48v (27 + 48v + 5v2) = 0 Solving 27 + 48v + 5v2 = 0 Solving for variable 'v'. Factor a trinomial. (9 + v)(3 + 5v) = 0Subproblem 1
Set the factor '(9 + v)' equal to zero and attempt to solve: Simplifying 9 + v = 0 Solving 9 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + v = 0 + -9 Combine like terms: 9 + -9 = 0 0 + v = 0 + -9 v = 0 + -9 Combine like terms: 0 + -9 = -9 v = -9 Simplifying v = -9Subproblem 2
Set the factor '(3 + 5v)' equal to zero and attempt to solve: Simplifying 3 + 5v = 0 Solving 3 + 5v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5v = 0 + -3 5v = 0 + -3 Combine like terms: 0 + -3 = -3 5v = -3 Divide each side by '5'. v = -0.6 Simplifying v = -0.6Solution
v = {-9, -0.6}
| 6x^3/24x^4 | | -23=45-4x | | 6g-3h= | | 3662x^5-21973x^4+52874x^3-63218x^2+37715x-8980=0 | | 20y^2+13y-15=0 | | 4x^2+28xy-18y= | | 14-7t=-56 | | 2x/3-16=-6 | | 13=y+3 | | X+49=3x-10 | | 6.0/2 | | 3x+2-15x=14y-6 | | -19-2d=11-8d | | -2s=-44+2s | | 7u-17=9u-5 | | 2x-90=-4x-18 | | -r-6r+2=86 | | 4x^4-9x^3= | | 6(p-10)-p=-40 | | -6y=-1-7y | | -17(12+w)=-7 | | (x-2)-12=(x-2)-12 | | (x-2)+y=(x-2)-12 | | -17=-2n+12-8n | | 18x^4/6x | | -60=-5(x+3) | | 26=-7q-6q | | 5/7v-3/2=-4/3 | | 15*5+4= | | 78=3c+10c | | x+6y=2x+y | | 10w-8w^2=0 |